Entrenamiento en uso de técnicas de gestión de stress y ansiedad en los trabajadores del sistema de protección a víctimas y testigos y otros implicados en el proceso penal, como medida preventiva ante el aparecimiento del Síndrome del Burnout. - Vinueza Chérrez, Luis Felipe (2016)
The present systematization report describes the processes regarding teaching cognitive restructure techniques for workers of the witness and victims protection system, among others involved in the penal process, such cognitive restructure techniques were conducted aiming to generate prevention plans against the BURNOUT syndrome. Anxiety and stress are related concepts since when they reach high levels they generate very similar physiological responses, despite the higher weight of the environmental causes for stress and psychological causes for anxiety during their corresponding beginnings. To establish this relation implies to understand that the person who handles high anxiety levels during a situation, will also face (without a proper intervention) high levels of stress. This high stress levels will generate what has been described as Burnout syndrome. Therefore, by intervening the anxiety, the Burnout syndrome can be prevented. The present report narrates the execution of those processes concerning teaching cognitive restructuration techniques. In addition, the results obtained during the performed intervention are described, schematizing also the effects achieved, as well as the events that took place during the intervention, mentioning the learning acquired from the experience.